HIGH SCHOOL STUDENTS’ RESPONSE TOWARD GUIDED INQUIRY TYPE PICTORIAL RIDDLE IN IMPROVING CRITICAL THINKING SKILLS - DAMAYANTI, FRANSISKA; JATMIKO, BUDI (Inovasi Pendidikan Fisika, 2018)
The lack of concern toward critical thinking skills affect the low rate of students? critical thinking skills. The research aim to describe the response of high school students toward guided inquiry type in improving students? critical thinking skills. This research conducted in 3 experiment classes of SMAN 1 Ngronggot. Instrument used in this research is response sheet contains 10 points of response. Data collected by giving response sheet to all students in three experiment classes after guided inquiry type pictorial riddle applied in learning. Collected data then analysed by response sheet analysis. Results show that based on response sheet analysis, students? response toward the implementation of guided inquiry type pictorial riddle in improving critical thinking skills is in very good category. Keywords: guided inquiry, pictorial riddle, critical thinking skills